2019
DOI: 10.1007/s13596-019-00394-w
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of Elateriospermum tapos seed extract against obese Sprague Dawley rats

Abstract: This study aimed to investigate the preventive role of Elateriospermum tapos seed extract against obese Sprague Dawley rats through assessment of bodyweight, caloric intake, organs weight, biological assays and histopathology. Thirty-six male Sprague Dawley rats were assigned into six groups of normal control (G1) group fed with standard chow diet, negative control (G2), positive control (G3) and treatment groups (G4, G5 and G6) were on high-fat and cafeteria diet for 9 weeks. G3 group was given 10 mg kg−1 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…According to the results, the HF and CAF diet-induced rats significantly gained weight as compared to rats fed with standard chow diet. These findings were similar to a previous study that showed body weight gain due to hyperphagia in rats [ 10 ]. Both energy-dense and palatable diets introduced to the rats contributed to fat hyperphagia and reduced sensitivity to peptide satiety, which resulted in overeating leading to obesity [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…According to the results, the HF and CAF diet-induced rats significantly gained weight as compared to rats fed with standard chow diet. These findings were similar to a previous study that showed body weight gain due to hyperphagia in rats [ 10 ]. Both energy-dense and palatable diets introduced to the rats contributed to fat hyperphagia and reduced sensitivity to peptide satiety, which resulted in overeating leading to obesity [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…With such consequences, natural resources have been used for obesity treatment on top of having lower toxicity, they also have fewer side effects, as compared to antiobesity drugs [ 5 , 10 ]. In the current study, we analyzed the anti-obesity activity of E. tapos shell extract in obesity-induced Sprague Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the filtrate underwent the freezedrying process to obtain an extract powder. E. tapos shell and seed powder were kept in a flacon tube and stored at under −20 °C [6].…”
Section: Elateriospermum Tapos Extractionmentioning
confidence: 99%